VARIABEL PEMBEDA KEPUTUSAN PENDANAAN JANGKA PENDEK, JANGKA MENENGAH DAN JANGKA PANJANG BAGI INDUSTRI MANUFAKTUR YANG LISTED DI BURSA EFEK INDONESIA - Ratnawati, Tri (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2008)
Discriminant analysis use for evidence to difference Short Term, Medium Term, Long Term Financing Decision, before crisis and at that moment of the crisis. Amount of the sample is 424 analysis unit of each, this result cause someone to repant Net Working Capital (NWC) and Leverage Short Term (LST) domination for Short Term Financing Decision, Profitability Medium Term (PMT) and Leverage Medium Term (LMT) domination for Medium Term Financing Decision and Dividend Payout Ratio (DPR) domination for Long Term Financing decision before and ant that moment of the crisis. Key Word: Financing Dicision, discriminant analysis, before crisis, at that moment of the crisis